Implementasi Traefik sebagai Reverse Proxy dengan Prinsip Zero Trust - Nuryasa, Arnanda; Suharjo, Imam (STMIK Banjarbaru, 2024)
Technology and application development are experiencing massive development, without realizing it, cyber crime is also increasing rapidly. The increase in cyber attacks is a concern and makes concerns about important data owned. The impact can make applications or services lose and important data can be stolen and misused. With the application of Treafik as one of the reverse proxies, it aims to be a solution in an effort to increase application security by integrating it with the development of an IP whitelist system that has Zero Trust Security principles. The method used in the development contains several stages of research, namely, system analysis, system design, configuration, and test scenarios. The results of testing and research show that the IP whitelist system runs well according to the system design and the application of traefic can improve the application security system by denying unrecognized access to the IP whitelist system with a